Computational Fluid Dynamics-Based Performance Evaluation of an Air Cooler for University Classroom Conditioning: A Case Study of Classroom E304, ITERA - Titis Pajar Ningsih; Nike Dwi Grevika Drantantiyas; Rizky Anisatul Khasanah; Muhammad Fadli Bagaskara; Zefanya Frandita Situmorang (Jurnal IPTEK, 2025)
The advancement of cooling technologies aims to enhance indoor comfort, but conventional air conditioners (AC) raise sustainability concerns due to high energy consumption. This study evaluated the performance of an air cooler in classroom E304, characterized by high occupancy and initial temperatures of 28–30°C with 55–57% relative humidity, exceeding comfort limits per SNI 03-6572-2001. After installing a single air cooler, CFD simulations indicated a temperature reduction to 22.50–23.08°C and relative humidity of 54.89–62.34%, within the comfort range. Model validation demonstrated high accuracy, with RMSE below 1°C and MAPE below 3%, confirming the simulation’s reliability for classroom cooling design. The results demonstrate that air coolers provide an effective and energy-efficient solution for tropical classrooms.